Arabic Calligraphy Identification for Digital Jawi Paleography using Triangle Blocks - Mohd Sanusi, Azmi; Omar, Khairuddin; Mohammad Faidzul , Nasrudin; Wan Mohd Ghazali, Khadijah; Abdullah, Azizi (2011)
Palaeography is the study of ancient handwritten manuscripts to date the age and to localize ancient and medieval scripts. It also deals with analysing the development of the letters shape. Ancient Jawi manuscripts are one of the least studied area. Nowadays, over 7789 known Jawi manuscripts are kept in custody of various libraries in Malaysia. Most of these manuscripts were undated with unknown authors and location of origin. Analysing the different types of writing styles and recognizing the manuscript illuminations can discover this important information. In this paper, we discuss the palaeographical analysis from the perspective of computer science and propose a general framework for that. This process involves investigation of Arabic influence on the Jawi manuscript writings, establishing the palaeographical type of the script, and classification of writing styles based on local and global Jawi image features.